Die nackte Insel - Hayashi, Hikaru 1931-2012 (Filmjuwelen, 2019)
The international breakthrough for one of Japan's most innovative filmmakers, who went on to make such other marvelous movies as Onibaba and Kuroneko. It follows a family whose home is on a tiny, remote island off the coast of Japan. They must row a great distance to another shore, collect water from a well in buckets, and row back to their island, a nearly backbreaking task essential for the survival of these people and their land
Extras: Booklet, Kinotrailer, weitere Highlights, Schuber
Original: Japan 1960
Bildformat 2.35:1 - 16:9 widescreen (schwarzweiß)
Keywords: Farmers / Japan / Drama; Islands / Japan / Drama; Film; DVD-Video